The effect of bearing and rearing a child on blood pressure: a nationally representative instrumental variable analysis of 444611 mothers in India - Teufel, Felix; Geldsetzer, Pascal; Sudharsanan, Nikkil; Subramanyam, Malavika; Yapa, H. Manisha; De Neve, Jan-Walter; Vollmer, Sebastian; Bärnighausen, Till (International journal of epidemiology, 2021)
At the individual level, it is well known that pregnancies have a short-term effect on a woman’s cardiovascular system and blood pressure. The long-term effect of having children on maternal blood pressure, however, is unknown. We thus estimated the causal effect of having children on blood pressure among mothers in India, a country with a history of high fertility rates.Bearing and rearing a child decreases blood pressure among mothers in India.As fertility continues to decline in India and similar countries, policy makers should design and implement hypertension screening and prevention programmes that specifically target women.Novel health programmes beyond antenatal care are needed to ensure that women without children receive blood pressure screening.We used nationally representative cross-sectional data from the 2015-16 India National Family and Health Survey (NFHS-4). The study population comprised 444 611 mothers aged 15-49 years. We used the sex of the first-born child as an instrumental variable (IV) for the total number of a woman’s children. We estimated the effect of an additional child on systolic and diastolic blood pressure in IV (two-stage least squares) regressions. In additional analyses, we stratified the IV regressions by time since a mother last gave birth. Furthermore, we repeated our analyses using mothers' husbands and partners as the regression sample.On average, mothers had 2.7 children [standard deviation (SD): 1.5], a systolic blood pressure of 116.4 mmHg (SD: 14.4) and diastolic blood pressure of 78.5 mmHg (SD: 9.4). One in seven mothers was hypertensive. In conventional ordinary least squares regression, each child was associated with 0.42 mmHg lower systolic [95% confidence interval (CI): -0.46 to -0.39, P < 0.001] and 0.13 mmHg lower diastolic (95% CI: -0.15 to -0.11, P < 0.001) blood pressure. In the IV regressions, each child decreased a mother’s systolic blood pressure by an average of 1.00 mmHg (95% CI: -1.26 to -0.74, P < 0.001) and diastolic blood pressure by an average of 0.35 mmHg (95% CI: -0.52 to -0.17, P < 0.001). These decreases were sustained over more than a decade after childbirth, with effect sizes slightly declining as the time since last birth increased. Having children did not influence blood pressure in men.Bearing and rearing a child decreases blood pressure among mothers in India.
Gesehen am 26.07.2021